Assessment of the impact of intravenous antibiotics treatment on gut microbiota in patients: Clinical data from pre-and post-cardiac surgery - Xue, Ling; Ding, Yinglong; Qin, Qiong; Liu, Linsheng; Ding, Xiaoliang; Zhou, Yi; Liu, Kun; Singla, Rajeev K.; Shen, Ke; Din, Ahmad Ud; Zhang, Yan; Shen, Zhenya; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Surgical site infection is a common complication after surgery. Periprocedural antibiotics are necessary to prescribe for preventing or treating infections. The present study aimed to explore the effect of intravenous antibiotics on gut microbiota and menaquinone biosynthesis in patients, especially in elderly patients undergoing cardiac surgery. A total of 388 fecal samples were collected from 154 cardiac surgery patients. The V3–V4 hypervariable region of the bacterial 16S rRNA gene was amplified and sequenced on a MiSeq PE300. The gut microbiota diversity of samples was analyzed in terms of α- and β-diversity at the OTU level. The different groups were classified according to antibiotics in combinations and single antibiotics. PICRUSt2 was used for preliminary prediction of the gut microbiota function for menaquinone biosynthesis. The composition of the gut microbiota had a significant change post-intravenous antibiotics treatment in all patients and elderly patients’ population. The intravenously administered antibiotics which are excreted via bile represents the main antibiotics that could disturb the gut microbiota’s composition in cardiac surgery patients, especially for elderly patients. The effect of antibiotics on gut microbiota is produced after antibiotics treatments over one week. The recovery of gut microbiota to the state of pre-antibiotics may require over two weeks of antibiotics withdrawal. The richness and diversity of gut microbiota are increased in elderly patients. Sex factor doesn’t represent as an influencer in gut microbiota composition. Long-term use of cefoperazone-sulbactam may affect coagulation function.